From the Religious Field to the Alternative Field: How Conspiracy Theories Challenge Differentiation - Bawidamann, Loïc (Journal of religion in Europe, 2024)
This article examines the link between religion and conspiracy theories by focusing on religious agents operating two alternative media outlets in Switzerland, opposing perceived mainstream opinions. Informed by Bourdieu’s field theory, the article elaborates on the agents’ surpassing of field boundaries, spawning an alternative field that accommodates all agents expelled from their initial fields. Through web scraping and qualitative interviews with the content creators, the analysis elucidates the particular significance of religious agents in the production and distribution of conspiracy theories, as they inherently oppose social differentiation, enabling them to contend with dominant authorities convincingly. The article concludes by offering an understanding of the alternative field and, by extension, of conspiracy theories as a process of dedifferentiation, striving for a realignment of the current structure of society.